Kaji Eksperimental Variasi Bentuk Injektor Udara Terhadap Pola Aliran Dan Debit Air pada Air-Lift Pump - Drajat Indah Mawarni (SIMETRIS, 2022)
Two-phase flow is two different fluid streams flowing in a pipe. Two-phase flows precipitate into gas-liquid, gas-solid, solid-liquid flows. Apart from the flowing fluid, two-phase flow is differentiated according to the direction of the vertical pipe and the direction of the horizontal pipe. The purpose of this study was to determine the pattern of flow and discharge in the air-lift pump through variations in the shape of the injector. This test was carried out with variations in the shape of the injector, namely the type of nozzle, tube and diffuser, using a test pipe with a vertical direction and a length of 500 mm with a diameter of 24 mm, using a water level of 450 mm with a superficial gas velocity of 0.07 m/s, 0.085 m/s , 0.10m/s. Of the injectors that have been carefully inspected, the nozzle-type injector with a superficial gas of 0.10 m/s produces the highest water discharge. While the lowest water discharge is found in the type of diffuser injector with superficial gas of 0.075 m/s. In observing the flow pattern of the injector nozzle the flow that occurs is (churn flow) but in each flow pattern there are several bubbles that appear. The flow patterns of tube injectors The flow patterns that occur are churn flow and annular flow. And in the diffuser injector, the flow pattern that occurs varies, namely churn flow and slug flow, the greater the superficial gas, the flow pattern changes to annular flow.